Reduced angle sensitivity of structural coloration on an industrial aluminium platform. (17th March 2020) - Odessey, Rachel; Shen, Tianyi; Oller, Declan; He, De; Kim, Jin Ho; Xu, Jimmy; Pacifici, Domenico
Abstract: Existing structural coloration methods using thin films, commonly implemented in high‐purity aluminium, produce colours which are highly dependent on the viewing angle because of the inherent angular dependence of thin film interference. Adapting the thin film coloration mechanism to anodisation of industrial‐quality aluminium alloys, which scatter light more efficiently than their high‐purity counterparts, reduces angle dependence in the colour produced. This reduction of angle dependence, as well as the wide use of anodised aluminium in consumer products, suggests that structural colour based on anodised aluminium could potentially be scaled up for commercial scale production.